Pengaruh Pelaksanaan Risk Based Internal Audit Terhadap Pencegahan Fraud - Susi Astuti; Agustina Riyanti (Owner : Riset dan Jurnal Akuntansi, 2025)
Fraud is currently a concern for business stakeholders in a company or institution, as many entities experience setbacks due to a lack of prevention and discipline over actions that can lead to fraud, resulting in a decline in public trust towards a company. Fraud is an illegal act committed intentionally to achieve certain goals, such as fulfilling the social needs of the perpetrator. Fraud can be committed by insiders or outsiders for personal, group, or factional gain. Financial statement fraud is the intentional or negligent misrepresentation of a material aspect of an organization by manipulating or engineering the financial statements. Therefore, the purpose of this research is to understand and analyze the role of risk-based internal audit in the context of fraud prevention efforts. This research uses the qualitative interpretive phenomenology method. Data collection in this study used interviews at RSUD Dr. Soedirman with a total of eight informants who served as internal auditors. The results of this study can be concluded that RSUD Dr. Soedirman Kebumen is at the risk enables level, meaning that RSUD Dr. Soedirman Kebumen has implemented a culture of fraud prevention. RSUD is a government agency, so it has clear regulations and guidelines in carrying out organizational activities.